Delayed management of blowout fractures: A case report on challenges and clinical recommendations - Hafiz, Al; Septiany, Dwi Tika (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2026)
Maxillofacial trauma is frequently encountered in emergency departments. Approximately 40% of orbital fractures are associated with concomitant maxillofacial fractures. Blowout fractures often result in both aesthetic and functional impairments. Clinical manifestations may include enophthalmos, hypoglobus, diplopia, ocular motility disorders, and visual disturbances. Optimal reconstruction is recommended within 14 days after trauma to prevent long-term sequelae. We reported a 24-year-old male patient diagnosed with a closed nasal bone fracture, deviated nasal septum, and orbital blowout fracture, with a month delayed since injury. The patient underwent endoscopic septorhinoplasty and orbital floor reconstruction utilizing a titanium plate and screw fixation. Proper and timely management of blowout fractures leads to satisfactory functional and aesthetic outcomes while significantly reducing the risk of permanent deformities. Delayed management of blowout fractures presents several challenges, including identifying orbital soft-tissue involvement, determining the optimal timing for intervention, and selecting appropriate implant materials. Clinical recommendations emphasize the importance of CT imaging and an integrated multidisciplinary approach involving ENT, ophthalmology, and radiology specialists to achieve the best possible functional and aesthetic outcomes for the patient.